DETERMINATION OF CARBON EMISSIONS WITH A GREEN MANUFACTURING APPROACH - Hadipranoto, Regina Valentrisa Sekariswari; Rimantho, Dino (ASTONJADRO, 2022)
A green manufacturing approach on production of bakso aci will give contribution for UMKM in process to find out the origins of environmental waste. This research has purposed to identify the origins and type of environmental waste in production process of bakso aci sekar at UMKM Sekar Group Bogor. The method used for this research are calculation with mass-balance and the emission with calculator carbon footprint. The data collecting process is carried out by observation and interview with the related person in UMKM Sekar Group Bogor. The waste identify results has show that environmental waste were found on production of bakso aci sekar. The results of show that environmental waste generated are CO2 Emission with a total of 0.18049 tons, water with a total of 10.5 Liters, material with a total of 0.482 Kg, and waste with a total of 0.5184 Kg. The identification of environmental waste with a green manufacturing approach will provide information for UMKM Sekar Group Bogor on process to find out the origins of environmental waste on their production process.